The Role of Violence within and across Self-identified Gang Youth - Vecchio, J. Michael (2014)
Within the field of criminology, increased attention has been afforded to the influence and importance of individual exposure to violence and victimization. Research has demonstrated that violence – whether actual or anticipated – is not distributed evenly across individuals, but is amplified during the period of adolescence and is strongly influenced by individual risky behavior. Perhaps for no other group has the role of violence been more pronounced than in the lives of gang affiliated youth. Whether actual (i.e., direct and vicarious victimization) or anticipated (i.e., fear of crime and perceived risk of victimization) violence, gang youth commonly discuss violence in terms of having an important role in both their gang experiences and daily lives. In particular, research has demonstrated how violence can play an important role within the specific stages of the gang experience – 1) gang joining, 2) active membership, and 3) gang leaving. This includes the importance of protection from violence as a common motivator for joining, the utility of violence as a means of building cohesion between active gang members, as well as the importance of exposure to violence as an impetus for gang leaving. While the role of violence is documented in the lives of gang youth, research has often approached the study of its influence and role in a disjointed and static manner. This has left a more fragmented understanding of the role of violence within specific stages of the gang experience. While further descriptive understanding of the role of violence within each stage of membership is needed, whether the role of violence changes over time or interacts across stages has largely been unexplored. This dissertation attempts to address this gap in the literature by using a mixed methods approach to examine and provide detailed descriptive accounts of the role of violence both within and across self-identified gang youth. This dissertation examines the role of violence within and across a sample of self-identified gang youth using both retrospective and prospective data. The objectives of the dissertation are: 1) to examine the prevalence and extent of objective (i.e., actual violence) and subjective violence (i.e., anticipated violence) within the three emergent domains (i.e., the neighborhood, school, and peer domains) as well as whether there are qualitative differences in violence between those who retrospectively discuss their self-identified status in terms of involvement in a gang or in a non-gang peer group; 2) to examine the extent and role of violence within each stage of membership (i.e., around the formation of gang ties, the period of active involvement, and the period of gang disassociation); and 3) to examine whether the role of violence varies over time or interacts across the tenure of gang involvement